Hybrid Technique for Improving the Watermarking and Encryption Scheme for Online Multimedia Copyright Protection to using Chaotic Maps Cryptography - Udayakumar, J; Prabakaran, G (International Journal of Computer Sciences and Engineering, 2025)
Encryption and watermarking are two innovative techniques that are used for protecting the traditional multimedia files. In this research paper, a proposed hybrid encryption-watermarking algorithm for content copyright protection is proposed. The watermarking steps of this proposed algorithm is based on combining the three techniques like Discrete Wavelet Transform (DWT), the Discrete Cosine Transform (DCT), and the Singular Value Decomposition(SVD), while the encryption phase is based on using different chaotic maps with different dimensions to improve the performance of algorithms efficiency. The proposed watermarking scheme uses a new PN-codes for embedding strategy of the watermark into the cover image. This scheme allows to decreasing the embedding strength factor of the scheme to a value that maximizes imperceptibility performance, while maintaining acceptable robustness and imperceptibility measures of the watermarking scheme. The performance of the proposed watermarking scheme is implemented individually based on the metrics like robustness and the imperceptibility measures. This scheme is compared with some very recent existing algorithms and experimental results show the improvements of the proposed algorithm over other important algorithms. On the other hand, the proposed chaos-based encryption algorithms used different chaotic maps of different dimensions to improve the performance of algorithms efficiency. The proposed encryption algorithm is tested using different set of experiments. The experimental results demonstrate that the proposed encryption algorithm research shows advantages of large key space, high resistance against differential attacks and high security analysis such as (i)Statistical analysis, and (ii)Sensitivity analysis. Compared to some traditional and recent encryption algorithms, our proposed encryption algorithm is much more secure. Finally experimental test demonstrate that the proposed hybrid encryption-watermarking algorithm introduces high degree of efficiency, robustness, and security as compared to previously developed techniques/algorithms